Increased Durability of Concrete Against High Temperatures due to Fire with Ground Granulated Blast Furnace Slag - Sumargo; Nursyafril; Ahmad Hamas Sorimatua Harahap (Department of Civil Engineering, Politeknik Negeri Bandung, 2021)
This paper describes experimental results that focus on impacts of elevated temperature on concrete with GGBFS. GGBFS from waste of steel factory PT Krakatau Steel Tbk. has been discovered to be appropriate for geopolymer cement as substitute for cement in concrete. Normal concrete and GGBFS concrete beams (150×150×750mm) and cylindrical (150×300mm) with 40% GGBFS content as substitute of cement weight were burned for two hours, which the first beam was burned at 600°C, second beam at 700°C and third beam at 800°C. After cooling to room temperature, cylindrical and beams were tested. Compressive strength, modulus of elasticity and flexural strength were examined and compared. The results show that GGBFS increased durability of concrete and might be utilized in applications including elevated temperatures. High temperature exposure causes compressive strength of normal concrete decreased extremely up to 69.08%, compared to GGBFS concrete only 46.21%. Flexural strength decreased to 30.37% when the temperature rises to 700°C. Furthermore, it decreased significantly to 50.82% when the temperature reached 800°C.